Penerapan Pembelajaran Berdiferensiasi pada Materi Klasifikasi Makhluk Hidup - Sujatmiani, Sujatmiani (Jurnal Didaktika Pendidikan Dasar, 2024)
The learning that has been practiced by teachers has not paid attention to differences in students’ learning styles. The aim of this research is to describe how differentiated learning is implemented to meet the different learning styles of students in the material on the classification of living creatures in class VII A of SMP Negeri 5 Kepil for the 2022/2023 academic year. This research is a qualitative descriptive study with research subjects totaling 25 students. The differentiated learning carried out also utilizes Smartphone technology in the form of using the Plant Net application for plant taxonomic identification. The results of the research show that the differentiated learning carried out has accommodated the different learning styles of students, including visual, auditory and kinesthetic learning styles.